Acoustic emission enabled particle size estimation via low stress-varied axial interface shearing - Yu,M; Reddyhoff,T; Dini,D; Holmes,A; O'Sullivan,C (IEEE Transactions on Instrumentation and Measurement, 2022)
Acoustic emission (AE) refers to a rapid release of localized stress energy that propagates as a transient elastic wave and is typically used in geotechnical applications to study stick-slip during shearing, and breakage and fracture of particles. This article develops a novel method of estimating the particle size, an important characteristic of granular materials, using axial interface shearing-induced AE signals. Specifically, a test setup that enables axial interface shearing between a one-dimensional compression granular deposit and a smooth shaft surface is developed. The interface sliding speed (up to 3mm/s), the compression stress (0-135kPa), and the particle size (150μm-5mm) are varied to test the acoustic response. The start and end moments of a shearing motion, between which a burst of AE data is produced, are identified through the variation of the AE count rates, before key parameters can be extracted from the bursts of interests. Linear regression models are then built to correlate the AE parameters with particle size, where a comprehensive evaluation and comparison in terms of estimation errors is performed. For granular samples with a single size, it is found that both the AE energy related parameters and AE counts, obtained using an appropriate threshold voltage, are effective in differentiating the particle size, exhibiting low fitting errors. The value of this technique lies in its potential application to field testing, for example as an add-on to cone penetration test systems and to enable in-situ characterization of geological deposits.